SOSIALISASI PENGEMBANGAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN INTERAKTIVITAS BELAJAR SISWA DALAM IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU SD/MI WAHAU BARU - Husnaeni; Anjani Putri Belawati Pandiangan; Totok Adhi Prasetyo; Qatrunnada Jinan Akmaliah; Sarwinda Rohmadani; Nirmala Agustina; Sulistia Wahyuningsih; Azmi Aziz; Riska Febriana; Sarniati Sarniati; Zakaria Pratama; Ilham Ahmad Mukhlisun; Lelan Purnama Sari; Maya Puspita Sari; Nunik Adriani (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2026)
The implementation of the Merdeka Curriculum demands a shift in the learning paradigm toward a process that is student-centered, meaningful, and interactive. One relevant approach to addressing these demands is the deep learning approach, which emphasizes active student engagement, deep understanding, and the development of higher-order thinking skills. However, in practice, teachers' conceptual understanding of the deep learning approach is still uneven, particularly in rural areas. This Community Service (PKM) activity aims to enhance the understanding of elementary school/madrasah ibtidaiyah teachers in Wahau Baru Village, Muara Wahau District, regarding the concepts and application of deep learning as a strategy to increase student learning interactivity in the implementation of the Merdeka Curriculum. The implementation method for the PKM was carried out thru socialization activities, including material presentations, interactive discussions, question-and-answer sessions, and learning reflections. The results of the activities showed a positive response and high enthusiasm from the participants, as well as an increase in teachers' understanding of the concept of deep learning. The teacher realized that the learning practices they had been using, such as discussions and project-based learning, were part of a deep learning approach that could be developed more structuredly. This activity contributes to strengthening teachers' readiness to implement more interactive, meaningful, and aligned learning that adheres to the principles of the Merdeka Curriculum. Thus, the socialization of deep learning development becomes a strategic step in improving the quality of the learning process in Wahau Baru Village Elementary School.